2013
DOI: 10.1007/s40279-013-0090-5
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Stress on Physical Activity and Exercise

Abstract: Background Psychological stress and physical activity (PA) are believed to be reciprocally related; however, most research examining the relationship between these constructs is devoted to the study of exercise and/or PA as an instrument to mitigate distress. Objective The aim of this paper was to review the literature investigating the influence of stress on indicators of PA and exercise. Methods A systematic search of Web of Science, Pub-Med, and SPORTDiscus was employed to find all relevant studies focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
671
3
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 865 publications
(733 citation statements)
references
References 382 publications
(577 reference statements)
43
671
3
16
Order By: Relevance
“…One should therefore consider that the strong relationship between depression and stress may in part be accounted for by some overlap in core symptoms (40). Finally, perceived stress may also lead to unhealthy behaviors, such as smoking, alcohol consumption, unhealthy dietary choices (41,42) and a sedentary lifestyle (43), which might also be implicated in the development of chronic conditions. Of note, it was not possible to adjust for some of these important lifestyle factors, which may have influenced the relationships that we observed between stress and chronic conditions and multimorbidity.…”
Section: General Findingsmentioning
confidence: 99%
“…One should therefore consider that the strong relationship between depression and stress may in part be accounted for by some overlap in core symptoms (40). Finally, perceived stress may also lead to unhealthy behaviors, such as smoking, alcohol consumption, unhealthy dietary choices (41,42) and a sedentary lifestyle (43), which might also be implicated in the development of chronic conditions. Of note, it was not possible to adjust for some of these important lifestyle factors, which may have influenced the relationships that we observed between stress and chronic conditions and multimorbidity.…”
Section: General Findingsmentioning
confidence: 99%
“…Exercise reduces stress perception through improving one's ability to cope with stress. [8] Exercise in any form can increase the body's production of the brain's feel-good endorphins. One of those being serotonin which improves mood, energy level, sleep, and promotes self-confidence.…”
Section: Introductionmentioning
confidence: 99%
“…Stress may decrease the efforts to be physically active (Stults-Kolehmainen & Sinha, 2014). Single parents of children with cancer have reported that they stay indoors for long periods of time, without being able to be active (Klassen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%